Droplet digital RT-PCR method for SARS-CoV-2 variants detection in clinical and wastewater samples - Wang, Feng; Sun, Yi; Gong, Liming; Su, Lingxuan; Zhou, Biaofeng; Lou, Xiuyu; Chen, Yin; Shi, Wen; Mao, Haiyan; Zhang, Yanjun (Frontiers in Microbiology, 2025)
ObjectiveTo establish a sensitive, specific, and precise quantitative detection method for SARS-CoV-2 variants using droplet digital RT-PCR (RT-ddPCR).MethodsDual primer-probe sets targeting the SARS-CoV-2 nucleocapsid (N) and spike (S) genes were designed. The annealing temperature for RT-ddPCR was optimized using a gradient PCR system. The sensitivity, defined as the limit of detection (LOD), was determined by serially diluting SARS-CoV-2 RNA. The specificity of the RT-ddPCR assay was evaluated using SARS-CoV-2 variants and common respiratory viruses. Precision and repeatability were assessed by quantitatively repeating the detection on serial dilutions of SARS-CoV-2 RNA. Additionally, the results of RT-ddPCR for clinical and environmental wastewater samples were compared with those from RT-qPCR.ResultsThe optimal annealing temperature was 53.5°C. The LOD for the N and S genes of the original SARS-CoV-2 strain was 4.26 (95% CI: 3.12–9.89) and 3.87 (95% CI: 2.77–7.75) copies/reaction. The Delta strain exhibited LODs of 4.65 (N gene, 95% CI: 3.28–9.64) and 6.12 (S gene, 95% CI: 4.33–15.59) copies/reaction. The Omicron showed 4.07 (N gene, 95% CI: 3.11–6.26) and 4.58 (S gene, 95% CI: 3.43–7.40) copies/reaction. Importantly, the RT-ddPCR assay was repeatable with a coefficient of variation of less than 10% when RNA concentrations of SARS-CoV-2 were between 73.50 and 7,500 copies/reaction. The high specificity of the RT-ddPCR assay was demonstrated by its ability to correctly detect the thirty SARS-CoV-2 variants, while not other common respiratory viruses. For 148 clinical pharyngeal swab specimens, the positive rate for both RT-ddPCR and RT-qPCR was 86.49%, and a coincidence rate of 98.65% and a Kappa value of 0.94. Quantitative comparison of RT-ddPCR and RT-qPCR in 50 wastewater samples with low viral load, RT-ddPCR assay detected 50 positives for dual gene targets (N and S genes), whereas RT-qPCR assay only 21 exhibited concurrent positivity for dual gene targets, while 25 showed S gene detection, and 4 were negative for dual gene targets, suggesting our RT-ddPCR assay enabled absolute quantification of SARS-CoV-2 variants with low viral load.ConclusionThe RT-ddPCR assay developed in this study can be used for SARS-CoV-2 variants detection and quantitative analysis of clinical and environmental samples.